2009
DOI: 10.1007/s10517-009-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycine on the Microcirculation in Rat Mesenteric Vessels

Abstract: Model experiments on biomicroscopy of mesenteric microvessels in laboratory rats were performed to evaluate the effect of natural metabolites (e.g., amino acid glycine) on the microcirculation. The effect of glycine was determined from a change in the diameter of arterioles. Application of glycine (0.1 ml, 1 M) to the mesenteric surface was followed by arteriolar dilation (by 50-80%). Histamine-induced disturbances in the microcirculation were not observed after preapplication of glycine. Under these condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
3
0
5
Order By: Relevance
“…Несмотря на то что результаты исследований моделей ишемии головного мозга на животных указывают на важ-ную роль оксидантного стресса при реперфузион-ном повреждении, доказательства реперфузионного повреждения при инсульте у человека ограниченны. В некоторых исследованиях с применением магнит-но-резонансной томографии (МРТ) при инсульте у человека с использованием режима с подавлением сигнала свободной воды (FLAIR) и перфузионно-взвешенной МРТ (ПВ-МРТ) было показано, как реперфузия может быть связана с ранним повышени-ем проницаемости гематоэнцефалического барьера и, следовательно, с вторичным реперфузионным по-вреждением и неблагоприятным исходом [9,10].…”
Section: Study Limitationsunclassified
See 2 more Smart Citations
“…Несмотря на то что результаты исследований моделей ишемии головного мозга на животных указывают на важ-ную роль оксидантного стресса при реперфузион-ном повреждении, доказательства реперфузионного повреждения при инсульте у человека ограниченны. В некоторых исследованиях с применением магнит-но-резонансной томографии (МРТ) при инсульте у человека с использованием режима с подавлением сигнала свободной воды (FLAIR) и перфузионно-взвешенной МРТ (ПВ-МРТ) было показано, как реперфузия может быть связана с ранним повышени-ем проницаемости гематоэнцефалического барьера и, следовательно, с вторичным реперфузионным по-вреждением и неблагоприятным исходом [9,10].…”
Section: Study Limitationsunclassified
“…As an example in human stroke, some MRI studies using fluid-attenuated inversion recovery and perfusion-weighted images have shown how reperfusion could be linked to an early opening of the blood-brain barrier and consequently to secondary reperfusion injury and poor outcome. 9,10 ROS generated during ischemia/reperfusion can react with unsaturated lipids of biomembranes, thereby generating malondialdehyde (MDA), an end-product of lipid peroxidation. MDA could be a biomarker of tissue injury and reflect oxidative damage; indeed, several studies have shown increased MDA concentrations in acute stroke patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fi rst studies demonstrated microcirculatory effect of glycine solution on mesenteric microvessels and on pial arterioles in laboratory rats [4][5][6]. A capacity of glycine to restore impaired microcirculation in the arterioles of the rat mesenterium under histamine induced infl ammatory alterations was shown revealing it's great, but little studied yet, antiinfl ammatory potential [5]. Effect of glycine on pial arterioles has been performed by using the original direct biomicroscopy with "open window" technique [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the tests used for an assessment of Glycine direct vasodilatory effect is an intravital biomicroscopy of pial microvessels in a brain of laboratory rats. The fi rst studies demonstrated microcirculatory effect of glycine solution on mesenteric microvessels and on pial arterioles in laboratory rats [4][5][6] …”
mentioning
confidence: 99%